Análisis de la relación entre la infección por Helicobacter Pylori y el desarrollo de gastropatías. - Dutan Vargas, Katherine Paulina (2025)
Helicobacter pylori is a bacterium estimated to be present in half of the human population. It seeks to colonize the gastric mucosa, where it can persist for years and elicit a chronic inflammatory response in the host. Therefore, the objective of this investigation was to analyze the relationship between Helicobacter pylori infection and the development of gastropathies through a systematic literature review. The review methodology was based on the PRISMA 2020 guidelines, encompassing articles published between 2020 and 2025, in Spanish and English, with full text available online and focused on the human species. These criteria yielded 21 studies that met the requirements. The search was conducted across three databases: PubMed, SciELO, and the Regional Portal of the Virtual Health Library. From these sources, it was determined that H. pylori exhibits a high prevalence in diverse populations, and its virulence factors—CagA, VacA, OipA, and DupA—are associated with the severity of gastric inflammation, determining progression to premalignant and malignant lesions. Furthermore, infection is consistently linked to gastritis, atrophy, metaplasia, peptic ulcers, and an increased risk of cancer. This investigation concludes that H. pylori is a determining factor in the genesis and progression of gastropathies.